Learning Beyond Borders: The Teaching of English for Refugees in Jakarta Learning Centers During COVID-19 - Sulistyowati, Lilis; Dewi, Ratna Sari; Alek, Alek (UIII Press, 2024)
Proficiency in English is essential for refugees as it significantly impacts their integration, social inclusion and self-reliance. In temporary host countries like Indonesia, refugees are keen to learn English before resettlement, but the COVID-19 pandemic hindered this process. Nevertheless, efforts to maintain English education at learning centers continued. What were the experiences of refugees learning English during COVID-19, and how did they navigate access to education amid the pandemic? This qualitative study examines refugees’ experiences in learning English during COVID-19 and their access to education. It focuses on two learning centers managed by Human Initiative (HI), a UNHCR partner organization in Greater Jakarta. Data was collected through interviews with UNHCR staff, Human Initiative employees, refugee students and volunteer teachers, along with class observations. The findings reveal that English instruction functions as a vital support system for refugees. The curriculum was adapted to accommodate their needs, with materials sourced online and Communicative Language Teaching (CLT) methods applied to improve speaking skills. The study also highlights the obstacles faced by students, teachers, and management as well as highlighting their adaptive and flexible strategies for maintaining education in difficult circumstances.